Novel Corona Virus (COVID-19): Assessing Prevalence of SARS-CoV-2 and Infection - Ehsan Hooshyar; Sarah Hosseini (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: The World Health Organization (WHO) declared severe acute respiratory syndrome coronavirus 2 a pandemic on March 11, 2020. Corona virus disease 2019 (COVID-19) is commonly transmitted from human-to-human via close contacts and touching surfaces. Reports indicated that many medical staff got infected on working with infected individuals. Likewise, dentists are at a higher risk for the virus transmission due to close proximity to patients and the nature of dental procedures. Despite all of the protections and disinfections, there were some reports of infected dentists.Purpose: In this study, we evaluated the prevalence of infected dentists and the rate of using protection protocols by them in Iran.Materials and Method: This survey was a cross-sectional descriptive and web-based study in which a questionnaire designed and uploaded on Google forms. The link of the form was shared among dentists in Iran via some social media groups and personal messages.Results: A total of 945 dentists participated in this survey. A higher proportion of participants had their own private practice. About one third reported fatigue, malaise, or headaches since the COVID-19 got epidemic in Iran. Most of the respondents had provided emergency and elective dental treatments, used face shields, and surgical masks. The 26.3% of respondents were positive for COVID-19.Conclusion: According to our analysis, about 26% of dentists had been infected with COVID -19 and most of them reported that they used the CDC's currently recommended infection prevention and control procedures in dental offices. However, the prevalence of infection was higher than prevalence of infection in the whole population of Iran (approximately 1%) and it showed that dentists were at high risk despite using infection control and personal protection equipment (PPE).